Thermal cycling distortion of porcelain fused to metal fixed partial dentures - (:unkn) unknown (MOSBY-ELSEVIER, 1998)
Statement of problem. The initial fit of porcelain fused to metal restorations deteriorates during the firing cycle of porcelain. Purpose. This study evaluated thermal cycling distortion of 3-unit porcelain fused to metal frameworks at different firing stages. Material and methods. A master model was designed to represent the 2 abutments of a 3-unit fixed partial denture replacing a missing mandibular molar. Standard techniques were used to fabricate 10 castings. Half of the copings were cast in a Ni-Cr alloy and the other half in a Pd-Cu alloy Framework distortion was measured by means of inner fit changes, horizontal linear measurements of the framework length, and vertical fit changes of each retainer. Measurements were made (1) initially, (2) after degassing firing, and (3) after glaze firing. Differences between the firing cycles created distortion values of the retainers in 3 dimensions. Repeated measures ANOVA was used to analyze data statistically. Results. Measured differences between the 2 firing stages ranged from -47 to 81.7 mu m. For both alloy groups, retainers showed increase in vertical gap that implied poorer vertical fit after porcelain application. Mean values of inner fit change recorded for porcelain application firing were higher in magnitude than the values of metal-conditioning firing. In addition, no statistically significant differences were found among alloy types. Conclusions. A 3-dimensional distortion was observed both in Pd-Cu and Ni-Cr frameworks during porcelain firing cycle. The distortion seen after porcelain application fir was significantly greater than that seen after metal-conditioning firing. This result can be attributed to these factors, contamination of porcelain to the inner surface of metal coping and reduction in resilience of metal.
Keywords: CERAMIC CROWNS; MARGIN DESIGN; FIT; RESTORATIONS